African Catholic : decolonization and the transformation of the Church - Foster, Elizabeth Ann, 1976- (USA : President and fellows of harvard college, 2019)
Makes original contributions to French history, African history, the history of Catholicism, and religious studies. The book approaches the history of late colonialism and decolonization in French sub-Saharan Africa from an entirely new political and cultural perspective, by examining it through the prism of religion. Drawing on a plethora of African and French voices, it brings to life a Franco-African Catholic world that had been forged by conquest, colonization, missions, and conversions, and still exists today. Its denizens were preoccupied with the future of France's African colonies, the place of Catholicism in Africa, and whether their personal loyalties should lie with the Vatican, France, or emerging African states. Many leading African intellectuals were Catholics, and the book shows that there was an important Catholic strand of the negritude movement, which has been completely ignored by scholars and impacted the church at the highest levels. This finding contributes to the book's new, striking story of Catholic reform at mid-century, showing how decolonization was a pivotal factor in the reorientation of the church at Vatican II.--
Introduction: Catholic conversations at the end of empire -- Postwar winds of change: church and state in French Africa -- A truly universal church: Alioune Diop and Catholic negritude -- Theologies of colonization: debating the legitimacy of empire -- Entirely Christian and entirely African: Catholic African students in France -- Men of transition: African clergy in postwar French Africa -- Foe or friend? Catholics and Islam on the eve of independence -- Slavery and charity: connecting French Catholics to Africa -- Conclusion: Decolonization and Vatican II.
Includes bibliographical references and index.
Keywords: Catholic Church -- Africa -- History; Catholic Church -- History -- 1965-; Decolonization -- Africa, French-speaking -- History; Decolonization -- Africa, Sub-Saharan -- History; Christianity and culture -- Africa, French-speaking -- History; Christianity and culture -- Africa, Sub-Saharan -- History